2011
DOI: 10.1364/josaa.28.002540
|View full text |Cite
|
Sign up to set email alerts
|

Scaling law for computational imaging using spherical optics

Abstract: The resolution of a camera system determines the fidelity of visual features in captured images. Higher resolution implies greater fidelity, and thus greater accuracy when performing automated vision tasks such as object detection, recognition, and tracking. However, the resolution of any camera is fundamentally limited by geometric aberrations. In the past, it has generally been accepted that the resolution of lenses with geometric aberrations cannot be increased beyond a certain threshold. We derive an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…We may consider using other optical elements, such as adaptive templates [41], artificial insect eyes [28], [27], and multiplexed configurations [55], as and when they become widely available in small, low-power form factors. In particular, curved sensors [31], [33], [17] are increasingly becoming a reality. In Fig.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…We may consider using other optical elements, such as adaptive templates [41], artificial insect eyes [28], [27], and multiplexed configurations [55], as and when they become widely available in small, low-power form factors. In particular, curved sensors [31], [33], [17] are increasingly becoming a reality. In Fig.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…It was shown that the sapphire ball lens has a better imaging quality and higher refractive index [22], which could improve the lateral resolution and decrease the noise. Also by using spherical sensor arrays with a spherical ball lens, uniform spatial resolution [23] and gigapixel resolution can be reached [24].…”
Section: Image Source Target Corresponding Pixel Area For Magnetic Beadsmentioning
confidence: 99%
“…Knowledge of these different imaging platforms' aberrations allows users to predict the achievable resolution, and permits system designers to correct aberrations either actively through adaptive optics or passively with post-detection image deconvolution. Digital aberration removal techniques play an especially prominent role in computational imaging platforms aimed at achieving simple and compact optical arrangements [2]. A recent important class of such platforms is geared towards efficiently creating gigapixel images with high resolution over a wide fieldof-view (FOV) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Digital aberration removal techniques play an especially prominent role in computational imaging platforms aimed at achieving simple and compact optical arrangements [2]. A recent important class of such platforms is geared towards efficiently creating gigapixel images with high resolution over a wide fieldof-view (FOV) [2,3]. Given the well-known linear scaling relationship between the influence of aberrations and imaging FOV [4], it is critical to characterize their effect before camera throughput can be successfully extended to the gigapixel scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation